Structure of financial systems and development of innovative enterprises with high growth potential - Balcerzak, Adam P. (Publishing House of the Wrocław University of Economics, 2009)
The aim of this paper is to analyze the influence of the financial system transformation on the development of new highly innovative enterprises with high growth potential. It is also an attempt to assess the government’s role in this context. Besides that, the role of venture capital as a specific part of financial system that provides financial support for the most innovative enterprises is presented. The paper presents synthetically the process of evolution of modern financial systems and its influence on abilities to finance young innovative enterprises. The growing role of open systems that enable to finance business ventures on financial markets is a significant phenomenon. As a result enterprises may be less dependent on traditional banking financing. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 30-39